2017
DOI: 10.1684/epd.2017.0914
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic bilateral transfrontal minimal radiofrequency thermocoagulation of the amygdalohippocampal complex for bilateral medial temporal lobe epilepsy: a retrospective study of 12 patients

Abstract: Background. Some patients with temporal lobe epilepsy have bilateral discharges and a few have bilateral medial temporal sclerosis. Stereotactic bilateral radiofrequency thermocoagulation (RFTC) of the amygdalohippocampal complex can terminate seizures or reduce seizure severity in patients with bilateral medial temporal lobe epilepsy (BMTLE). Aim. To explore the safety and efficacy of bilateral transfrontal minimal RFTC of the amygdalohippocampal complex for the treatment of BMTLE. Methods. A total of 12 BMTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Several clinical studies evaluating LiTT have been published over the past years. Most of them reported the seizure outcome following LiTT in patients with MTLE . Although the seizure‐free rate varied across the series, the results following LiTT might be close to those reported in patients who undergo selective hippocampo‐amygdalectomy .…”
Section: Discussionmentioning
confidence: 70%
“…Several clinical studies evaluating LiTT have been published over the past years. Most of them reported the seizure outcome following LiTT in patients with MTLE . Although the seizure‐free rate varied across the series, the results following LiTT might be close to those reported in patients who undergo selective hippocampo‐amygdalectomy .…”
Section: Discussionmentioning
confidence: 70%
“…Of the 373 reviewed abstracts and studies, a total of 37 studies dealing with thermal ablation (18 MRgLITT studies and 19 RFA studies) were closely analyzed. Finally, 13 studies dealing with MRgLITT [21][22][23][24][25][26][27][28][29][30][31] and six dealing with RFA [32][33][34][35][36] were included (Figure 1). For ATL and sAHE, four RCTs 4,37-39 and 20 comparative studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] were included.…”
Section: Resultsmentioning
confidence: 99%
“…60 Zhao et al reported on 12 patients with bilateral ablation of the temporal lobes and could demonstrate a significant improvement at the group level in all scales of the Wechsler Adult Intelligence Scale-Revised (WAIS-R) as well as the Wechsler Memory Scale-Revised, except the delayed recall. 32 In contrast, Lee et al could not detect a significant difference in WAIS-R at 6 months after RFA. 61 Neuropsychological data at an individual level were found in six of the open surgery studies and were summarized.…”
Section: Neuropsychological Outcomementioning
confidence: 90%
“…A recent meta-analysis that included 6 studies [19,22,24,26,27,32] and a total of 296 patients found a seizure-free rate of 23% and a responder rate of 58% one year after the SEEG-guided RF-TC, responders being defined as those with 50% or greater reduction in seizure frequency as compared to the pre-procedure period [30]. At the study level, meta-regression failed to identify factors impacting the seizurefree rate, including the number of RF-TC.…”
Section: Outcomementioning
confidence: 99%
“…Alongside surgical advances in conventional epilepsy surgery, stereotactic lesioning has emerged as an alternative when surgery is not an option. Several stereotactic approaches have been developed, including radiosurgery [6], Laser Interstitial Thermotherapy (LiTT) [7][8][9][10][11][12][13][14][15], High Intensity Focal Ultrasound (HIFU) [16,17], and SEEG-guided Radiofrequency Thermo-Coagulation (SEEG-guided RF-TC) [18][19][20][21][22][23][24][25][26][27]. The present review focuses on the latter, which aims at coupling SEEG investigation with RF-TC stereotactic lesioning directly through the recording electrodes.…”
Section: Introductionmentioning
confidence: 99%